2001
DOI: 10.1021/np000474b
|View full text |Cite
|
Sign up to set email alerts
|

Onnamide F:  A New Nematocide from a Southern Australian Marine Sponge, Trachycladus laevispirulifer

Abstract: A southern Australian marine sponge, Trachycladus laevispirulifer, has yielded a potent new nematocide with antifungal activity which has been identified as onnamide F (1). The structure for 1 was assigned by detailed spectroscopic analysis and chemical conversion to the methyl ester 2. Onnamide F contains a common structural motif previously described in a number of natural products exhibiting interesting pharmacological activities, including the insect chemical defense agent pederin (3), and the sponge metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…100,[173][174][175][176][177][178] Structurally, they are remarkably similar to pederin 26, discussed above, and many compounds exhibit similarly potent cytotoxicities. However, unlike 26 they do not appear to exert any dermatotoxic effects.…”
Section: Onnamides and Theopederinsmentioning
confidence: 79%
“…100,[173][174][175][176][177][178] Structurally, they are remarkably similar to pederin 26, discussed above, and many compounds exhibit similarly potent cytotoxicities. However, unlike 26 they do not appear to exert any dermatotoxic effects.…”
Section: Onnamides and Theopederinsmentioning
confidence: 79%
“…However, to bring the full story to its climax, one has to return to the marine environment, as in the years from 1988 to early 2000, a significant number of sponge extracts produced molecules such as the onnamides, with onnamide F being an example (15), 30 and theopederins such as K and L (16,17). 31 Then, in 2002, Kellner 32 identified the endosymbiont as a very close relative to Pseudomonas aeruginosa and showed that interspecific transmission of the endosymbionts was related to the different genetic makeup of individual isolates.…”
Section: Brazilian Paederus Beetles and Marine Sponge Metabolitesmentioning
confidence: 99%
“…A signal at δ C 158.0 was assigned as a guanidine carbon of arginine, and this analysis confirmed close relationship with the bioactive metabolites known as theopederins, [12][13][14] mycalamides, [15][16][17][18] and onnamides. [19][20][21][22] (Fig. 2).…”
mentioning
confidence: 95%
“…14 (subclass Tetractinomorpha, order Lithistida, family Theonellidae), and Trachycladus laevispiralifer (subclass Tetractinomorpha, order Axinellida, family Spirastrellidae). 22 Reports on isolation of pederin class of compounds from taxonomically distant organisms indicate the possible microbial origin of the compounds.…”
mentioning
confidence: 99%